الاتصال التنظيمي ودوره في تحسين فعالية التنظيمية لدى العمال المتعاقدين - قحيز, محمد; منيعي, بلقاسم; عيشوش, إسماعيل (جامعة الوادي university of Eloued, 2022)
الملخص: تحاول الدراسة الراهنة تقصي موضوع الاتصال التنظيمي و دوره في تحسين الفعالية التنظيمية للمؤسسة، وذلك من خلال الوقوف على واقع كلا المتغيرين في المؤسسة قيد الدراسة، وابراز أهم أشكال الاتصال التنظيمي التي لها دور في تحسين الفعالية التنظيمية، وانطلقت دراستنا من تساؤل رئيسي هو: "فيما يتمثل الدور الذي يلعبه الاتصال التنظيمي في تحسين الفعالية التنظيمية في المؤسسات؟". وقد تم تحديد المنهج المستخدم في الدراسة وهو المنهج الوصفي وأدوات جمع البيانات بالارتكاز على الاستمارة، حيث تم القيام بمسح شامل على موظفي الضمان الاجتماعي شملت 45 موظف . بالاعتماد على مجموعة من المعالجات الاحصائية باستخدام برنامج التحليل الإحصائي على أسئلة الدراسة واختبار فرضياتها، بالإضافة الى مناقشة النتائج مع فرضيات الدراسة، ومن خلاله تحققت الفرضيات الجزئية الثلاث، وهو ما أثبت صدق الفرضية الرئيسة محل الدراسة حيث يلعب الاتصال التنظيمي دورا في تحسين الفعالية التنظيمية في مؤسسة الضمان الاجتماعي. وقد توصلت الدراسة إلى النتائج التالية: أن الاتصال الرسمي له دور كبير في تحقيق أهداف المؤسسة، أن الاتصال غير الرسمي له تأثير واضح في تحقيق التكيف والاندماج بين العاملين، تبادل المعلومات له دور في زيادة الأداء بين العاملين. Abstract : The current study attempts to investigate the issue of organizational communication and its role in improving the organizational effectiveness of the institution, by examining the reality of both variables in the institution under study, and highlighting the most important forms of organizational communication that have a role in improving organizational effectiveness, and our study started from a main question: What role does organizational communication play in improving organizational effectiveness in organizations? The method used in the study was determined, which is the descriptive approach and data collection tools based on the questionnaire. A comprehensive survey was conducted on social security employees, which included 45 employees. Relying on a set of statistical treatments using the statistical analysis program on the study questions and testing its hypotheses, in addition to discussing the results with the hypotheses of the study, and through which the three partial hypotheses were achieved, which proved the validity of the main hypothesis under study, where organizational communication plays a role in improving organizational effectiveness in an institution. Social security. The study reached the following results: that formal communication has a major role in achieving the goals of the institution, that informal communication has a clear impact in achieving adaptation and integration among workers, and the exchange of information has a role in increasing performance among workers..
دراسة ميدانية في مؤسسة الضمان الاجتماعي
مذكرة ماستر علم الاجتماع تخصص علم اجتماع التنظيم والعمل
Keywords: الاتصال التنظيمي، الفعالية التنظيمية; Organizational communication, organizational effectiveness; Communication organisationnelle, efficacité organisationnelle